2009
DOI: 10.1097/mbc.0b013e328313fc8e
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of haemophiliacs with inhibitors in France: orthopaedic status, quality of life and cost – the ‘Statut Orthopédique des Patients Hémophiles’ avec Inhibiteur study

Abstract: The physical condition of severe haemophilia and the impact of advances in replacement therapy have been much studied, but little work has been done on patients who developed inhibitors. The 'Statut Orthopédique des Patients Hémophiles avec Inhibiteur' study was conducted in France in order to assess the orthopaedic status and quality of life of such patients, and the cost of their medical management. Fifty haemophiliacs aged 12-63 years with a history of high-responder inhibitors were included. Clinical asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…In addition, the use of standardized scales for anxiety and depression screening was also a distinguishable feature of this investigation. Most studies in haemophilia field report anxiety/depression levels based on mental health subscales of health‐related quality of life questionnaires, on self‐reports of presence of anxiety/depression, or on unstandardized questions developed for the purpose of specific studies . The results of this investigation advance the knowledge on factors associated with anxiety and depression among PWH, drawing relevant conclusions to inform interventions aiming to promote well‐being among these patients.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the use of standardized scales for anxiety and depression screening was also a distinguishable feature of this investigation. Most studies in haemophilia field report anxiety/depression levels based on mental health subscales of health‐related quality of life questionnaires, on self‐reports of presence of anxiety/depression, or on unstandardized questions developed for the purpose of specific studies . The results of this investigation advance the knowledge on factors associated with anxiety and depression among PWH, drawing relevant conclusions to inform interventions aiming to promote well‐being among these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Further searching of reference lists gave a total of 195 potentially relevant publications. Based on further analysis of these results, 26 publications from 24 studies were identified for inclusion in this review [12–37].…”
Section: Resultsmentioning
confidence: 99%
“…Less common were qualitative studies (structured interviews or focus‐group sessions), or studies based on medical examination, physical testing, retrospective case review or a surveillance programme. Most studies made use of a single type of methodology, although four studies used questionnaires plus one other technique (semi‐structured interviews [12], medical examination [13], physical testing [14] or review of medical records [15,16]). All but two studies were based in a single country and reported national data from a European country, Australia, Iran or the USA; the exceptions were a pan‐European study that included data from 21 countries [15] and a questionnaire validation study that included patients from six European countries [17].…”
Section: Resultsmentioning
confidence: 99%
“…Hemophiliac arthropathy in the lower limb joints (knee and ankles), causes significant alterations in gait and function [32,33]. The effectiveness of the interventions analyzed, regarding the improvement of these two variables allows us to support the suitability of applying, within the usual clinical protocol, the guidelines described in the articles included in this review.…”
Section: Discussionmentioning
confidence: 99%